Development of recombinant oncolytic Coxsackievirus B3 for treatment of colorectal carcinoma - Hazini, Ahmet (My University, 2018)
Colorectal cancer is one of the most death related cancer type in worldwide. Conventional cancer therapeutics show curable effect only in the patients at early stage of the disease. In case of the diagnosis at late stages, the survival rate decreases dramatically up to 10%. Therefore, novel cancer therapeutics are urgently needed. Oncolytic virotherapy is a new treatment approach which exploits the viruses against cancer. Clinical trials prove the efficiency of various oncolytic viruses in treatment of different tumors. Coxsackievirus B3 (CVB3), a single-stranded RNA virus of the picornavirus family, has been described as a novel oncolytic virus against lung carcinoma. However, CVB3 can induce severe diseases, such as pancreatitis, myocarditis and encephalitis, but the course of infections is decisively influenced by the particular strain of CVB3. In this thesis, firstly, it was aimed to investigate different laboratory strains of CVB3 (Nancy, 31-1-93, H3) which use the coxsackievirus and adenovirus receptor (CAR) and the strain PD which uses N- and 6-O-sulfated heparin sulfate (HS) for entry into colorectal tumor cells, for their potential to lyse these cells and for their safety profile. In vitro investigations showed variable infection efficiency and lysis of colorectal carcinoma cell lines by the CVB3 strains. The most efficient strain was PD, which was the only one that could lyse all five of the investigated colorectal carcinoma cell lines. Lytic activity of CAR-dependent CVB3 did not correlate with CAR expression on colorectal carcinoma cells, whereas there was a clear correlation between lytic activity of PD and its ability to bind to HS at the cell surface of these cells. Intratumoral injection of CVB3 Nancy, 31- 1-93 or PD into subcutaneous colorectal DLD1 tumors in BALB/c nude mice each resulted in strong inhibition of tumor growth. The effect was seen in the injected tumor, as well as in a non-injected, contralateral tumor. However, all animals treated with 31-1- 93 and Nancy developed systemic infection and died or were moribund and sacrificed at 6 and 8 days post intratumoral virus injection. In contrast, five of the six animals treated with PD showed no signs of a systemic viral infection and PD was not detected in any organ. These results indicate that PD has potential to be a potent and safe oncolytic CVB3 strain for use in the treatment colorectal carcinoma. To increase the tumor selectivity, so that to abolish the possibility of undesirable virus infection in healthy organs, target sites of pancreas-specific microRNA was inserted into the virus genome and recombinant CVB3 was analyzed in vitro and in vivo. Detargeting of the pancreas, which is the most susceptible tissue for CVB3 infection, by exploiting miRNAs, increased the survival rate of treated animals significantly. The virus was unable to replicate in the pancreas and all animals survived. In contrast, colorectal carcinomas were destroyed as efficient as the wild-type CVB3. Finally, it was aimed to increase the efficiency of CVB3 against infection resistant colorectal cancer cell line by using directed evolution strategy. Results showed that CVB3 can specifically adapted to colorectal carcinomas leading to breaking the resistance of the tumor cells against CVB3 infection.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2018
Keywords: Colorectal Carcinoma; Coxsackievirus B3; Oncolytic Virotherapy; RNA interference; Virus adaptation